Correlation of Cord Blood Lipid Profile with Neonatal Gender and Mode of Delivery - Ninghot, Abhijit; Ansari, Azmat Kamal; Ansari, Shabana Andleeb; Asif, Mohammad; Hiware, Sanket Dadarao; Mohod, Kanchan (Asian Journal of Medical Research, 2018)
Background: Several studies have suggested that both genetic and environmental factors influence the composition of cord blood lipids. As dyslipidemia is associated with increased predisposition to atherosclerotic diseases, we planned to study effect of gender and mode of delivery on cord blood lipid profile. Subjects and Methods: We carried out a hospital based cross sectional study including 200 normal healthy neonates and compared cord blood lipid profiles (Total cholesterol (TC), Triacylglycerol (TAG), High Density Lipoprotein Cholesterol (HDL), Low Density Lipoprotein Cholesterol (LDL) and Very Low Density Lipoprotein Cholesterol (VLDL) between male and female neonates as well as neonates delivered by normal vaginal delivery and caesarean section. Results: No statistically significant (p values > 0.05) difference was observed between cord blood lipid profiles of groups of neonates based on both gender (p value of 0.654 for TC, 0.541 for TAG, 0.457 for HDL, 0.647 for LDL and 0.541 for VLDL) and mode of delivery (p values of 0.904, 0.907, 0.830, 0.910 and 0.907 for TC, TAG, HDL, LDL and VLDL respectively). Conclusion: The study indicates that cord blood lipid profile is not significantly affected by gender and mode of delivery of neonates.